Demographic and Clinical Characteristics of Hypertensive and/or Diabetic Patients with Target Organ Damage in the Lebanese Population - Kekedjian, Jeannot; Challita, Raymond; Abdallah, Mikael Abi; Asmar, Roland; Chahine, Mirna N (Archives of Clinical and Biomedical Research, 2020)
Background: Hypertension and diabetes represent a major public health problem. They are associated with complications, organ damage, and an increase in cardiovascular mortality. Objective: The aim of this study was to analyze the demographic and clinical characteristics of hypertensive and/or diabetic patients with target organ damage in the Lebanese population. Methods: Retrospective cross-sectional multicentric study conducted on 750 Lebanese patients randomly selected from 6 hospitals from January 2014 to August 2015. Patients were divided according to their medical history: 252 hypertensive, 249 diabetic, 249 both hypertensive and diabetic. All patients had target organ damages and were admitted to the hospitals. Results: Our study showed the following demographic characteristics: men were affected more than women; young men and older women being more commonly affected in each gender subgroup; hypertension was associated with older age compared to diabetes. It also showed the following clinical data: hypertension was associated with higher risk of cardiovascular diseases, higher systolic blood pressure, and left ventricular hypertrophy; diabetes was associated with higher incidence of nephropathy, dyslipidemia and cardiovascular diseases (if positive family history); having both diseases was associated with developing atherosclerotic plaques. Conclusion: Our study demonstrated an increased prevalence of affected Lebanese men (by both diseases) in the younger population, and increased prevalence of Lebanese women in the older population (> 75 years old). Family history of previous cardiovascular diseases was present in all groups. Disease recurrence, as defined in our study by the number of existing cardiovascular diseases, was more common in patients with both diseases.